1998
DOI: 10.1111/j.1600-0684.1998.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of type‐1 and type‐2 T‐helper immune responses in HIV‐1 vaccine protection

Abstract: The dichotomy of type-1 and type-2 T-helper (Th) immune responses is thought to be an obstacle to develop Human immunodeficiency virus-type- (HIV-1) vaccines capable of inducing effective cellular as well as humoral immune responses. Macaca mulatta were immunized using two different HIV-1sf2 envelope vaccine strategies, based on either immune-stimulating complexes (ISCOM) or chimeric Fowlpox (FP) vaccines. One month following the third immunization all animals were heterologously challenged with simian/human i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…This vaccine induced potent gp120-specific IFN-␥, IL-2, and IL-4 responses, indicating that both type 1-and type 2-like responses were elicited. These findings are in agreement with those of previous studies with ISCOMs in which both CTL as well as NA responses were induced in rhesus macaques and vaccine protection was observed (21,22). In contrast, potent NA responses were also induced by rgp120/MF59 immunization, but the T-helper responses after the first two immunizations, in particular IFN-␥ and IL-2, were weak.…”
Section: Discussionsupporting
confidence: 92%
“…This vaccine induced potent gp120-specific IFN-␥, IL-2, and IL-4 responses, indicating that both type 1-and type 2-like responses were elicited. These findings are in agreement with those of previous studies with ISCOMs in which both CTL as well as NA responses were induced in rhesus macaques and vaccine protection was observed (21,22). In contrast, potent NA responses were also induced by rgp120/MF59 immunization, but the T-helper responses after the first two immunizations, in particular IFN-␥ and IL-2, were weak.…”
Section: Discussionsupporting
confidence: 92%
“…Antigen‐specific proliferative T‐cell responses were detected in monkeys immunized with an ISCOM TM ‐based vaccine containing influenza virus antigen 47 . In addition, ISCOM TM ‐based vaccines formulated with HIV‐1 gp120 or HIV‐1 multicomponent antigens (gp120, p24, V2 and V3 peptides) have been shown to prime T cells, resulting in proliferation and cytokine secretion (IL‐2, IL‐4 and IFN‐γ) 19 , 50 , 51 , 52 . Importantly, both formulations efficiently protected monkeys against challenge with chimeric simian/human immunodeficiency virus (SHIV).…”
Section: Properties Of Iscomtm‐based Vaccinesmentioning
confidence: 99%
“…The initiation of an immune response is dependent on a subcutaneous (s.c.) innate immune system encompassing pro-in¯ammatory cytokines. Studies in our laboratory 13±15 have shown that iscoms are potent inducers of such cytokines and, in particular, IL-1, IL-6 and IL-12, but also betachemokines like MIP-1 alpha, MIP-1 beta, and RANTES are stimulated to production in primates, at least by iscoms carrying gp120 of HIV-1 16,17 Iscoms induce CTL as well as Th1 and Th2 type of t cells…”
Section: How Do Iscoms Prime Immune Response?mentioning
confidence: 99%